Erasmus the Educator: Moral Reformation and Pedagogy in Light of the Philosophia Christi. Issue 2 (August 2018) - Powell, Justin
Erasmus is famous as the humanist scholar who helped shape what became modem education. W. H. Woodward and Erika Rummel have written standard works on his life and teachings, and others offer nuanced analysis. This article hopes to fill a small gap in Erasmus studies in that his "philosophy of Christ", which finds its roots in the Early Church Fathers, is directly related to his pedagogy.